On‐chip dielectrophoretic recovery and detection of a lactate sensing probiotic from model human saliva. Issue 3 (7th December 2022) - Hamilton, Sean; Shea, Delaney; Ibsen, Stuart; Brasino, Michael
Abstract: Early detection has led to increased survival for multiple cancers; however, the 5‐year survival rate of oral carcinoma (OC) has remained at 40% for the last several decades. Screening for OC is routinely done via visual examinations, followed by tissue biopsy and laboratory testing. Point‐of‐care testing would be a more convenient and widely available alternative for at‐risk individuals. Increased lactate production is a hallmark of many head‐and‐neck tumors, due to the Warburg Effect, where tumor cells favor glycolysis in the place of oxidative phosphorylation. To detect excess lactate, we have modified the commensal bacterium Escherichia coli Nissle 1917 to express fluorescent reporter genes in response to extracellular lactate. Administering this commensal as a mouth wash and subsequently collecting saliva for the detection of the reporter may allow for noninvasive, early detection of cancerous lesions in at‐risk individuals. Furthermore, we demonstrate a new on‐chip electrokinetic technique to recover these probiotic probes from model saliva fluid to improve the detection of reporter gene activation.